Did States' Adoption of More Rigorous Standards Lead to Improved Student Achievement? Evidence From a Comparative Interrupted Time Series Study of Standards-Based Reform. (June 2022) - Song, Mengli; Garet, Michael S.; Yang, Rui; Atchison, Drew
This study was designed to assess the effects of states' adoption of more rigorous standards as part of the current wave of standards-based reform on student achievement using comparative interrupted time series analyses based on state-level NAEP data from 1990 to 2017. Results show that the effects of adopting more rigorous standards on students' mathematics achievement were generally small and not significant. The effects on students' reading achievement were also generally small, but negative and statistically significant for Grade 4. The study also revealed that the effects of states' adoption of more rigorous standards varied across NAEP subscales and student subgroups.